Biochemical and genetic analyses of immune response towards acute hepatopancreatic necrosis in disease tolerant Penaeus monodon / Christie Soo Tze Chiew - Christie Soo , Tze Chiew (2022)

(untitled)
Shrimp aquaculture industry has long overtaken wild capture fisheries as the main supplier of freshwater and marine shrimps globally. However, even until now, disease has remained the top concern of shrimp aquaculture farmers as it has significantly reduced the growth of production in aquaculture industry. There exists a shrimp bacterial disease, known as Acute Hepatopancreatic Necrosis Disease (AHPND) by which the pathogen involved is a unique Vibrio parahaemolyticus bacteria strain (VpAHPND). This disease can lead to mass mortalities in shrimp ponds within early post-stocking days. Intriguingly, different shrimp species demonstrated different levels of immune tolerance or resistance towards AHPND infection. For better understanding of this matter, this study was conducted to identify the immune response triggered in disease tolerant Penaeus monodon upon AHPND infection and the underlying genetic factors or forces that resulted in differing immune tolerance between shrimp species. The disease tolerant P. monodon shrimps were exposed to VpAHPND bacteria through immersion method and sampled at time points of 0, 3, 6, 12, 24, 36, and 48 hours post-infection (hpi). The physiological and immunological changes of disease tolerant P. monodon after AHPND infection were observed and validated. Biochemical tests, including Phenoloxidase, Respiratory Burst, Superoxide Dismutase, Nitrite Concentration, Calcium Concentration, Total Haemocyte Count, and Bradford Assay were conducted. This was followed by 16S amplicon sequencing of P. monodon gut samples. In addition, important immune-related Differentially Expressed Genes (DEGs) were determined through transcriptome analysis of P. monodon hepatopancreas samples at 3, 6, and 24 hpi together with uninfected control. The gene expressions were further determined and validated using qPCR analysis. Subsequently, nucleotide sequences of selected immune-related genes were obtained through PCR and Sanger Sequencing. The trimmed sequences were then analysed using various genetics software for evolutionary genetics, phylogenetic, and molecular clock tracing analyses. Gross clinical symptoms of AHPND disease such as empty stomach, empty gut, and damaged hepatopancreas were observed. The biochemical tests validated the immunological activation of VpAHPND-infected P. monodon especially at 6 and 12 hpi. The gut microbiome changes of P. monodon caused by AHPND infection were determined at phylum, family, and genus levels. Based on the gene expression analysis results, an interactive innate immune response pattern was deduced to be activated at hepatopancreas of VpAHPND-infected P. monodon. Pathogen-Associated Molecular Patterns (PAMPs) were detected by Pattern Recognition Receptors (PRRs) which then led to downstream immune cascade reactions mainly involving immune signalling genes, antimicrobial peptides, antioxidants, and Damage-Associated Molecular Patterns (DAMPs). From the evolutionary genetic analysis, significant genetic divergence between the compared gene group sequences was identified. Purifying selection was uncovered to be the main evolutionary force acting on M. rosenbergii and disease tolerant P. monodon. Balancing selection was deduced to have occurred during AHPND infection. The divergence times for selected immune genes were estimated to be within the Paleozoic era which was after the famous Cambrian explosion. In conclusion, the information obtained in this study can provide insights for future shrimp functional and evolutionary genomics studies.